2016
DOI: 10.3389/fpls.2016.01628
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene Potentiates Sulfur-Mediated Reversal of Cadmium Inhibited Photosynthetic Responses in Mustard

Abstract: The potential of exogenous ethylene and sulfur (S) in reversal of cadmium (Cd)-inhibited photosynthetic and growth responses in mustard (Brassica juncea L. cv. Pusa Jai Kisan) were studied. Plants grown with 50 μM Cd showed increased superoxide and H2O2 accumulation and lipid peroxidation together with increased activity of 1-aminocyclopropane carboxylic acid synthase (ACS) and ethylene production and inhibition of photosynthesis and growth. Application of 1 mM SO42- or 200 μL L-1 ethephon (ethylene source) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 70 publications
(93 reference statements)
12
66
0
Order By: Relevance
“…In the present study, NO decreased content of H 2 O 2 and TBARS showing the capability of NO in mitigation of salt-induced oxidative stress (Table 1). These findings are in accordance with the earlier reports by Bai et al (2011), Fatma et al (2016 and Per et al (2017), that NO application alters the antioxidant system and protects plants against salt stress.…”
Section: Treatmentssupporting
confidence: 94%
See 4 more Smart Citations
“…In the present study, NO decreased content of H 2 O 2 and TBARS showing the capability of NO in mitigation of salt-induced oxidative stress (Table 1). These findings are in accordance with the earlier reports by Bai et al (2011), Fatma et al (2016 and Per et al (2017), that NO application alters the antioxidant system and protects plants against salt stress.…”
Section: Treatmentssupporting
confidence: 94%
“…Salt stress decreased chlorophyll content, maximum quantum efficiency of PSII photochemistry (Fv/Fm), electron transport and quantum yield of PSII, with partial stomata closure (Steduto et al , Mehta et al ). Earlier research has shown the reduction in chlorophyll fluorescence and disruption of antenna pigments by the barrier of electron transport flow from PSII to PSI under heavy metal stress (Parmar et al , Khan et al ). In the present study, application of NO improved Fv/Fm, Fv′/Fm′, ΦPSII, qP and ETR, however, non‐photochemical quenching (NPQ) was reduced (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations